The Relationship Between Hypertension and Body Mass Index on Rheumatic Cases at The Elderly - Kurniani Fatma Hardini; Indra Cahyadinata; Alfian Noha Zulkarnain; Mochammad Syafrie Ardhabily; Falina Nur Khaula (University of Muhammadiyah Malang, 2025)
Indonesia is experiencing a rapid increase in its elderly population, accompanied by a rising burden of chronic conditions. Elevated body mass index (BMI) has been identified as a potential risk factor for musculoskeletal problems. However, evidence at the community level in rural Indonesia remains limited. This study aimed to examine the relationship between BMI, blood pressure status, and rheumatologic complaints among elderly individuals in Balonggemek Village, Jombang Regency. This study employed a cross-sectional analytical observational design. Spearman’s correlation coefficient was used to analyze the relationship between BMI, blood pressure, and rheumatologic complaints. The majority of participants were classified as obese based on BMI assessment. Knee and hip pain were the most commonly reported rheumatologic complaints. Spearman’s correlation analysis showed a significant positive relationship between BMI and rheumatologic complaints.